Sorry, I Should Have Checked the Culture First : An exploration into the use of cultural context related to social orientations in interpersonal apologies - Kenny, Samantha Christine (MacEwan University Student eJournal, 2020)
Humans make mistakes, and as a result, apologies are an inescapable aspect of intercultural communication. This paper suggests that cultural pragmatics are the foundation for an effective apology. Through a content analysis of sources, the key contextual factors that impact an apology are individualism-collectivism orientations, rooted in the social values of different cultures. Some of the key findings proposed that these different orientations are exemplified in Japanese and American cultures, as they tend to focus on either the group or the individual in an apologetic situation. Apologies are not cross-culturally universal, but based on the pragmatics of cultural orientations, especially individualism-collectivism, they can be predicted. To examine this in the paper, apologies are defined in the context of universality, and Japan/the US are identified as cultures that present strong social contexts, requiring cultural context to create an apology. Then, the literature review establishes the importance of these socially based expectations through linguistics, social purpose, and saving face. The discussion section then argues that these concerns are more important than situational cues, that an individualistic orientation is less complicated to predict in regard to apologies, and that these pragmatic preparations prevent the escalation of the act being apologized for. In the conclusion, it is pointed out that even with these contextual clues, apologies are not entirely predictable, but these tools can help mitigate cultural misgivings.